Characterization of the Culturable Gut Microbiota of Two Colombian Main Malaria Vectors (2023)
ABSTRACT: Bacteria inhabiting the gut of malaria vectors can strongly influence their biology and competence to transmit Plasmodium parasites and other pathogens. This study aimed to isolate and characterize the culturable gut bacterial microbiota in two main Colombian malaria vectors. Anopheles (Diptera: Culicidae) darlingi Root, 1926 and Anopheles (Diptera: Culicidae) nuneztovari Gabaldón, 1940, specimens were collected in two malaria-endemic regions and under two feedings status. The bacterial composition was compared according to mosquito species, geography, and feeding status. Bacterial isolates from homogenized mosquito guts were morphologically and biochemically characterized, and their taxonomy was determined by 16S rRNA sequencing. Results showed that Gram-negative bacilli, particularly of the Proteobacteria phylum, are predominant in the gut of the two-vector species regardless of geography and feeding status. At the genus level, Enterobacter, Acinetobacter, and Bacillus were common among the two-vector species and geographic sites; and some genera were locality or vector-specific. In addition, the presence of blood in the mosquito gut negatively impacted bacterial richness at the genus level. These results advanced the knowledge of mosquito-microbe interactions for these malaria vectors. In addition, the generation of a bacterial culture repertoire may allow us to investigate the potential role of some bacteria as biocontrol agents.